2018
DOI: 10.1007/s00586-018-5541-0
|View full text |Cite
|
Sign up to set email alerts
|

Response rate does not affect patient-reported outcome after lumbar discectomy

Abstract: Higher response rates than seen in Swespine are not needed to achieve reasonably representative data on patient-reported outcome for large cohorts. Two-year data do not seem to add additional information. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
(35 reference statements)
10
25
1
Order By: Relevance
“…Furthermore, Elkan et al showed that RR did not affect PROM results after lumbar discectomy. 24 This indicates that a goal of 80% may not be necessary, but further studies are needed to determine an acceptable limit. The limit may also vary depending on the field, as previous studies have demonstrated significant differences between responders and non-responders both in demographic and in outcomes in various fields.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Elkan et al showed that RR did not affect PROM results after lumbar discectomy. 24 This indicates that a goal of 80% may not be necessary, but further studies are needed to determine an acceptable limit. The limit may also vary depending on the field, as previous studies have demonstrated significant differences between responders and non-responders both in demographic and in outcomes in various fields.…”
Section: Discussionmentioning
confidence: 99%
“…The current study analyzed a larger set of explanatory variables for a larger population, which might explain the inferential disparity. Elkan et al [5] compared differences in outcome between the Swespine disc hernia population and a cohort of disc hernia patients from a single hospital. In the latter group, the response rates were considerably larger than in the Swespine register.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of spine registers in the context of patient dropout has been tested before in Denmark, Norway and Sweden [3][4][5][6]. In these studies, the outcome for nonrespondents was assessed in either phone interviews or by postal questionnaires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although primary discectomy is an effective treatment for LDH with radiculopathy, a small proportion of patients (5%-15%) experience symptomatic recurrent LDH (rLDH), 19,46,47 and 4% to 6% undergo revision surgery within 2 years. [48][49][50] Techniques for management of recurrent herniation are dependent upon the specific patient indications and the surgeon's experience, on a case-by-case basis. Regardless of the reoperation strategy, clinical evidence has shown that patients who undergo revision surgery for symptomatic rLDH have worse clinical outcomes (eg, pain and disability) compared to patients who do not reherniate following primary discectomy.…”
Section: Prevention Of Recurrent Ldhmentioning
confidence: 99%